Cadmium isotope fractionation of materials derived from various industrial processes - Martinková, Eva; Chrastný, Vladislav; Francová, Michaela; Šípková, Adéla; Čuřík, Jan; Myška, Oldřich; Mižič, Lukáš (Journal of hazardous materials, 2016)
Our study represents ϵ(114/110) Cd NIST3108 values of materials resulting from anthropogenic activities such as coal burning, smelting, refining, metal coating, and the glass industry. Additionally, primary sources (ore samples, pigment, coal) processed in the industrial premises were studied. Two sphalerites, galena, coal and pigment samples exhibited ϵ(114/110) CdNIST3108 values of 1.0±0.2, 0.2±0.2, 1.3±0.1, -2.3±0.2 and -0.1±0.3, respectively. In general, all studied industrial processes were accompanied by Cd isotope fractionation. Most of the industrial materials studied were clearly distinguishable from the samples used as a primary source based on ϵ(114/110) Cd NIST3108 values. The heaviest ϵ(114/110) CdNIST3108 value of 58.6±0.9 was found for slag resulting from coal combustion, and the lightest ϵ(114/110) CdNIST3108 value of -23±2.5 was observed for waste material after Pb refinement. It is evident that ϵ(114/110) Cd NIST3108 values depend on technological processes, and in case of incomplete Cd transfer from source to final waste material, every industrial activity creates differences in Cd isotope composition. Our results show that Cd isotope analysis is a promising tool to track the origins of industrial waste products.
Keywords: Anthropogenic activities; Industrial waste products; Cadmium isotopes